Attention deficit hyperactivity disorder is associated with (a)symmetric tonic neck primitive reflexes: a systematic review and meta-analysis - Wang, Meng; Yu, Jing; Kim, Hyun-Duck; Cruz, Angelita Bautista (Frontiers in Psychiatry, 2023)
Introduction: Investigation on the association between attention deficit hyperactivity disorder (ADHD) and primary reflexes is in the initial stage, with considerable differences in the findings. This study evaluated the association between ADHD and primitive reflexes using systematic review and meta-analysis. Methods: Data were obtained from PubMed, Cochrane Library, Web of Science, EBSCO (Medical Literature Analysis and Retrieval System Online, American Psychological Association Psyclnfo, and Education Resources Information Center), Embase, Scopus, and ProQuest. Articles were searched from the date of inception of the respective databases to January 01, 2023, and StataCorp Stata (version 15) was used for the analysis. Results: Four articles with 229 samples were included in the meta-analysis. Results showed a significant positive and moderate correlation between ADHD and primitive reflexes, particularly asymmetric tonic neck reflex: summary r value= 0.48, 95% CI=0.27–0.64; symmetric tonic neck reflex: summary r value=0.39, 95% CI=0.25–0.52. The subgroup analysis indicated that the behavioral problem measuring tool (Conners’ scale), sex, and primitive reflex test can significantly moderate the association between ADHD and primitive reflexes. Conclusions: ADHD symptoms in children are closely related to the non-integration of primitive reflexes. Longitudinal or experimental studies should be conducted to reveal the causal relationship between ADHD and primitive reflexes in the future.